The golden braid - Dickerson, Melanie (Dickerson, Melanie. Hagenheim series, 2015)
Rapunzel can throw a knife better than any man. She paints beautiful flowering vines on the walls of her plaster houses. She sings so sweetly she can coax even a beast to sleep. But there are two things she is afraid her mother might never allow her to do: learn to read and marry. Fiercely devoted to Rapunzel, her mother is suspicious of every man who so much as looks at her daughter, and warns her that no man can be trusted. After a young village farmer asks for Rapunzel's hand in marriage, Mother decides to move them once again -- this time, to the large city of Hagenheim. The journey proves treacherous, and after being rescued by a knight -- Sir Gerek -- Rapunzel, in turn, rescues him farther down the road. As a result, Sir Gerek agrees to repay his debt to Rapunzel by teaching her to read. Could there be more to him than his arrogance and desire to marry for riches and position? As Rapunzel acclimates to life in a new city, she uncovers a mystery that will forever change her life. A world of secrets and treachery are about to be revealed after seventeen years. How will Rapunzel finally take control of her own destiny? And who will prove faithful to a lowly peasant girl with no one to turn to?